Pemanfaatan Media Digital dalam Meningkatkan Hasil Belajar Sejarah di SMA Negeri 1 Tualang - Dahnas , Israr; Kartika , Engkar; Suwarsih, Suwarsih (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the utilization of digital media in improving history learning outcomes at SMA Negeri 1 Tualang. The research employs Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection in two cycles. The subjects are 11th-grade students who face difficulties in understanding history through conventional teaching methods. Data were collected through observations, interviews, learning outcome tests, and documentation. The findings indicate that implementing digital media significantly enhances students' learning outcomes. In the first cycle, the average student score increased by 18%, while in the second cycle, it improved by 35%. The use of digital media, such as interactive videos, learning applications, and historical simulations, makes learning more engaging, facilitates concept comprehension, and increases student participation. This study concludes that digital media utilization is an effective strategy for improving history learning outcomes at the high school level.